2021
DOI: 10.3390/app11104589
|View full text |Cite
|
Sign up to set email alerts
|

Mode Shape-Based Damage Detection Method (MSDI): Experimental Validation

Abstract: The main principle of vibration-based damage detection in structures is to interpret the changes in dynamic properties of the structure as indicators of damage. In this study, the mode shape damage index (MSDI) method was used to identify discrete damages in plate-like structures. This damage index is based on the difference between modified modal displacements in the undamaged and damaged state of the structure. In order to assess the advantages and limitations of the proposed algorithm, we performed experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 31 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The numerical results of a fourteenstorey shear building and a six-storey laboratory building model showed that the proposed method was effective in quantifying damage. Duvnjak et al [123] proposed a new method to identify damage in plate-like structures. They established a damage index, namely the mode shape damage index (MSDI), based on the difference between the modal displacements before and after the structure was damaged.…”
Section: Mode Shape-based Methodsmentioning
confidence: 99%
“…The numerical results of a fourteenstorey shear building and a six-storey laboratory building model showed that the proposed method was effective in quantifying damage. Duvnjak et al [123] proposed a new method to identify damage in plate-like structures. They established a damage index, namely the mode shape damage index (MSDI), based on the difference between the modal displacements before and after the structure was damaged.…”
Section: Mode Shape-based Methodsmentioning
confidence: 99%
“…However, when the goal of the study is to know the variability of the elastic properties in different zones, it is necessary to include in the objective function Y (X) other dynamic properties such as modal shapes. The above is because the differences between the measured versus calculated modal shapes can better reflect local changes in the elastic properties of plate-like elements [39].…”
Section: Regional Sensitivity Analysismentioning
confidence: 99%
“…Studies based on bridge assessment have been performed by Jayasundara et al [23]. The CDF method [9,24] and the MSDI [25] could identify 2, 3, and 4 number of damaged member combinations, the possibility of a false signal exists in cases of extremely small damage. Additionally, if the damage number is larger, there is a risk of a false alert.…”
Section: Introductionmentioning
confidence: 99%